Effect of a mindfulness-based cognitive behavior therapy intervention on occupational burnout among school teachers - Paudel, Netra Raj; K. C., Prakash; Nygård, Clas-Håkan; Neupane, Subas (Frontiers in Psychiatry, 2025)
BackgroundWe aimed to assess the effect of mindfulness-based cognitive behavior therapy (MB-CBT) as an intervention to reduce burnout among secondary school teachers in Nepal.MethodsThe baseline survey of this randomized controlled trial included 218 secondary school teachers from 37 schools in Kathmandu. At a one-month follow-up, 192 teachers completed post-test survey. The Maslach Burnout Inventory for Educators (MBI-ES) tool was used to measure burnout in three dimensions: emotional exhaustion (EE), depersonalization (DP), and personal accomplishment (PA). Teachers in the treatment arm (n=102) received MB-CBT, while those in the control arm (n=116) continued their regular activities. Linear regression models with generalized estimating equations were used to calculate the mean, mean change estimates, and their 95% confidence intervals (CIs).ResultsThe mean level of EE decreased during the post-test for both treatment (mean change -0.93, 95% CI: -2.56 to 0.70) and control (-1.71, 95% CI: -3.24 to -0.18) arms. The mean level of DP also decreased in the treatment arm (-0.12, 95% CI: -0.98 to -0.75), but a sharper decline was observed in the control arm (-1.97, 95% CI: -2.78 to -1.16). The mean level of PA increased in both the treatment (1.04, 95% CI: -0.21 to 2.30) and control (1.53, 95% CI: 0.35 to 2.70) arms.ConclusionsThe prevalence of high EE and low PA decreased in both arms. However, the prevalence of high DP remained constant in the treatment arm but sharply decreased in the control arm. No significant differences between the arms were found in the post-test mean levels of EE, DP, and PA. The virtual MB-CBT intervention showed no significant impact on reducing burnout. Nonetheless, small reductions in burnout were observed in both groups.